Edukasi Gizi Isi Piringku dengan Media Komik pada Anak Siswa UPT SDN 060881 Medan - Agnes Sry Vera Nababan; Yulita Yulita; Winda Sauci Panjaitan (STIKES Columbia Asia Medan, 2024)
One of the efforts made by the government to overcome the problem of nutritional status is by campaigning Fill My Plate. Communication, Information and Education (KIE) on nutrition for school children can shape children's eating habits from an early age to achieve better individual conditions in the future. The role of nutrition education using media can help the process of sending nutrition messages and create motivation for targets so that the nutrition messages given can be well received. Elementary school age students tend not to like textbooks that are not accompanied by interesting pictures and illustrations, and empirically students tend to like picture books, and visualized in realistic or cartoon form. Comics have a good visual media function in helping to convey lesson material. The aim of this PKM is to provide education about the contents of my plate to elementary school students. Education is provided using comic media. The output of community service is in the form of comics and will be published in online media and community service journals.